Options and Challenges for Implementing Green Spaces in Urban Development. - Syrbe, Ralf-Uwe; Chang, Jiang (Springer, 2018)
Providing highly qualitative, healthy green areas in densely populated cities is often a serious challenge. Cities need to search for new and innovative solutions to increase public space with vital vegetation that we call urban green space.
Keywords: Stadtentwicklung; Grünraumplanung; Freiraumplanung; Verdichtungsraum; Siedlungsdichte; Ökologie; Nachhaltige Entwicklung; Transformation; Stadtgrün; Umsetzung; Stadtökologie; Stadtnatur; Biodiversität; Ökosystem; Internationaler Vergleich